2006
DOI: 10.1143/jjap.45.8586
|View full text |Cite
|
Sign up to set email alerts
|

Blue Luminescent Center and Ultraviolet-Emission Dependence of ZnO Films Prepared by Pulsed Laser Deposition

Abstract: ZnO thin films were grown on sapphire substrates at a growth temperature of 400 °C by Nd:yttrium–aluminum–garnet (Nd:YAG 1064 nm) pulsed-laser deposition. The effects of oxygen pressure on the structure, stoichiometric composition and optical properties of ZnO thin films were investigated in detail. X-ray diffraction (XRD) shows that the crystal quality is highest for the ZnO film grown at a pressure of 10 mTorr. Optical transmittance, electronic properties and Raman spectra show the increase in the stoichiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…The E 1 (LO) mode positioned at about 580 cm -1 attributable to the formation of zinc interstitials and oxygen vacancies is not found in this figure, suggesting relatively low defect density in these films [18,19]. For ZnO, the E 2 (high) mode frequency shifts relative to the single crystal value can be used to estimate residual stress in thin films [20,21].…”
Section: Resultsmentioning
confidence: 83%
“…The E 1 (LO) mode positioned at about 580 cm -1 attributable to the formation of zinc interstitials and oxygen vacancies is not found in this figure, suggesting relatively low defect density in these films [18,19]. For ZnO, the E 2 (high) mode frequency shifts relative to the single crystal value can be used to estimate residual stress in thin films [20,21].…”
Section: Resultsmentioning
confidence: 83%
“…Figures 9(a) 24) It can therefore be inferred that the shift of the Raman peak position of E1(low) involves some contribution of the lattice defects in the obtained ZnO nanoparticles. A steep increase in the Raman band around 1050 cm -1 was also observed with an increase in the concentrations of zinc nitrate hydrate from 0.01 mol/L to 0.1 mol/ L. Windisch, Jr. et al have also reported that the intensity of the Raman bands depends on the change in symmetry caused by defects.…”
Section: Jcs-japanmentioning
confidence: 79%
“…In this study, it can be estimated that the acceptor level of V zn locates at *0.40 eV above the valence band. The green emission 523 nm (*2.36 eV) are attributed to radiative transitions from the deep donor level of Zn i to acceptor levels caused by singly ionized V zn - [36]. Because the peak positions of the green emission are located at 2.36 eV in this study, the acceptor level of the ionized V zn -locates at *0.61 eV above the valence band.…”
Section: Micro-raman Studymentioning
confidence: 61%